Short pulse x-ray generation in synchrotron radiation sources - Martin, I; Ian Peter Stephen MARTIN (2011)
This thesis describes an investigation into the performance of different schemes for generating short x-rays pulses via synchrotron radiation emission. A review is given of the methods that have been previously proposed for this task. From this review, three leading schemes are selected for in-depth investigations, each of which explores the boundary of what is presently achievable in accelerator-based light sources. The first scheme generates short x-ray pulses by operating an electron storage ring in a quasi-isochronous state using a ‘low-alpha’ lattice. High and low emittance lattices are developed, studied through simulation and then implemented on the Diamond storage ring. Beam dynamics and bunch length measurements are presented for a variety of machine conditions, and an assessment is made of the minimum practically achievable bunch length for stable user operation. Radiation pulses of 1 ps r.m.s. are demonstrated using this scheme. The second and third schemes investigate performance limits for a linac-based light source through numerical simulations. The first of these generates ultra-short pulses by passing a highly compressed electron bunch through a long undulator to radiate in the ‘single-spike’ regime. A comparison is made with theoretical predictions for the required electron bunch length to operate in this way, which highlights the need for accurate start-to-end simulations. The final scheme generates ultra-short x-ray pulses through laser manipulation of the electron bunches. The modulated electrons pass through a long undulator with tapered gap, such that only the centre of the modulated portion experiences high free-electron laser (FEL) gain. A method to enhance the FEL output from this scheme using a wavelength filter and grating-compressor is investigated. The sensitivity of the two schemes to jitter sources is determined, and it is demonstrated both schemes are capable of generating GW-level, fully coherent sub-fs soft x-ray pulses. Such pulses would open up the development of time-resolved science to new regimes.